The CMEA attitude to a New Economic Order - Peter Knirsch (Intereconomics, 1978)
Insofar as the New International Economic Order (NIEO) is aimed at strengthening the national sovereignty of the developing countries, at eliminating their dependence upon external “imperialist“ markets, the Eastern bloc does indeed give very concrete expression to its support. The starting position is of course that any kind of intervention can only originate from the Western industrialized countries and never from the Soviet Union and the other CMEA countries are not willing to meet concrete demands for the reform as far as they are concerned.
Keywords: 330; Nieo